Człowiek z marmuru - Andrzej Wajda (Poland : Film Polski Film Agency, 1976)
Set in the mid-1970s, Poland, this film follows documentary filmmaker Agnieszka (Krystyna Janda) who begins to work on a film about Mateusz Birkut (Jerzy Radziwilowicz), a bricklayer who had briefly been hailed as a hero of the proletariat in the 1950s but then disappeared into obscurity. In piecing together details about the bricklayer's mysterious life, she discovers that his involvement in organized labor had been viewed negatively by party bosses, and that her own investigations could put her in danger.